Serum microRNA Profiles Serve as Novel Biomarkers for Autoimmune Diseases - Jin, Fangfang; Hu, Huanhuan; Xu, Ming; Zhan, Shoubin; Wang, Yanbo; Zhang, Huayong; Chen, Xi (Frontiers in Immunology, 2018)
Autoimmune diseases involve a complex dysregulation of immunity. Autoimmune diseases include many members (e.g., rheumatoid arthritis and systemic lupus erythematosus), and most of them are classified according to what organs and tissues are targeted by the damaging immune response. Many studies have focused on finding specific biomarkers for single autoimmune diseases, but so far, there are no universal biomarkers for detecting almost all autoimmune diseases. Serum miRNAs have served as potential biomarkers for the detection of various diseases. The aim of the present study was to find a universal biomarker for diagnosing autoimmune diseases. Regulatory T cells (Tregs) play pivotal roles in protecting an individual from autoimmunity, and depletion of Tregs in mice is considered a representative animal model of autoimmune disease. Two mouse models for Treg depletion, in which Treg was depleted by CD25mAb (in C57 mice) or by diphtheria toxin (in Foxp3DTR mice), were investigated, and 381 miRNAs were identified in the serum of mice with Treg depletion. A distinctive circulating miRNA profile was identified in Treg-depleted mice and in patients with autoimmune disease. RT-qPCR confirmation and ROC curve analysis determined that 6 miRNAs (miR-551b, miR-448, miR-9, miR-124, miR-148 and miR-34c) in the Treg-depleted mouse models and 3 miRNAs (miR-551b (specificity 73.5%, sensitivity 88.4%), miR-448 (specificity 82.4%, sensitivity 91.3%) and miR-124 (specificity 76.5%, sensitivity 91.3%)) in patients with rheumatoid arthritis, systemic lupus erythematosus, Sjogren’s syndrome and ulcerative colitis could serve as valuable biomarkers. These circulating miRNAs may represent potential universal diagnostic and prognostic biomarkers for autoimmune diseases.